Collaboration of health and education sectors drives equity for children with complex disabilities in China - Jacobs, Lisa; Gleason, Deborah; Gissara, Daniela; Congdon, Nathan; Smith, George; Xu, Peter (Frontiers in Public Health, 2023)
Medical professionals often find it challenging to assess children having both complex disabilities and visual impairment, which may lead to excluding such children from educational programs and limiting their full participation in family and community activities. Identification and assessment of these children are essential to close this exclusion gap. A five-year project in Shanxi province, China, provided comprehensive training to eye health providers and educators as they learned to assess, identify, refer and serve children with visual impairments, both with and without complex disabilities. A team of teachers, vision and general healthcare providers worked to assess the vision of these children at schools, residential settings, and in homes throughout Shanxi. The project led to deep collaboration between Shanxi's health and education sectors, and established replicable precedents for policy and system changes towards the inclusion of children with complex disabilities and visual impairment.